Exploration of treatment burden through examination of workload and patient capacity during transition onto kidney replacement therapy: a systematic review of qualitative research - Catrin Jones; Ross Cairns; Heather Walker; Silje Welsh; Benjamin Edgar; Karen Stevenson; Bhautesh D. Jani; Patrick B. Mark; David Kingsmore; Katie I. Gallacher (BMC Medicine)
Abstract Background Patients with advanced chronic kidney disease requiring initiation of kidney replacement therapy (KRT) are frequently asked to enact complex management plans. Treatment burden has been defined as the effect of healthcare workload and the capacity a person has to manage this workload has on wellbeing. The aim of this review is to examine the experience of healthcare workload and the factors that affect capacity to meet that workload for people transitioning onto KRT for the first time, using a framework synthesis of published literature informed by normalisation process theory (NPT) and theory of patient capacity (TPC). Methods Medline, Scopus and CINAHL were systematically searched with manual citation and reference searching. Studies were included if meeting the criteria of adults aged 18 or over transitioning for the first time onto any modality of KRT (haemodialysis, peritoneal dialysis or kidney transplantation), using qualitative methodologies to describe any aspect of experiences of healthcare workload or any factors that affect capacity to manage workload were included. Abstracts and full papers were independently screened by two reviewers and data extraction and quality appraisal were also independently conducted by two reviewers. Qualitative data were analysed using framework synthesis informed by NPT and TPC. Results A total of 24,380 studies were screened, 406 full texts were reviewed and 18 studies were included. There were four broad categories of workload described: making sense of KRT, working out what to do and how to do it, meeting the challenges of KRT, and reflecting on work done. Patient capacity influenced the experience of all types of workload and the treatment burden generated by the work. Conclusions Transitioning onto KRT is a period of very high healthcare workload and potentially high treatment burden. The relationship between healthcare workload and capacity to handle workload is complex, multifactorial and changes over time. By better understanding workload, capacity and burden during transition, we can develop better ways of measuring these important aspects of care and develop interventions to reduce treatment burden in those transitioning onto KRT.